2020
DOI: 10.1002/bmb.21341
|View full text |Cite
|
Sign up to set email alerts
|

An idea to explore: Use of augmented reality for teaching three‐dimensional biomolecular structures

Abstract: Biology and biochemistry students must learn to visualize and comprehend the complex three-dimensional (3D) structures of macromolecules such as proteins or DNA. However, most tools available for teaching biomolecular structures typically operate in two dimensions. Here, we present protocols and pedagogical approaches for using immersive augmented reality (AR) visors, specifically the Microsoft HoloLens, to reinforce learning with large scale 3D holographic structures. We developed a novel workflow to render v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 33 publications
0
34
0
4
Order By: Relevance
“…The use of AR technology in chemistry curricula has already shown pedagogical success in multiple reports, 12,[31][32][33][34] even through as far as we know they all involve only static content i.e. not featuring any molecular motions, interactions or any kind of interactivity as our website does, they do not stand web-accessible, most are rather limited in the number of available examples and activities, and a few require ad hoc peripherals.…”
Section: User Adoptionmentioning
confidence: 99%
“…The use of AR technology in chemistry curricula has already shown pedagogical success in multiple reports, 12,[31][32][33][34] even through as far as we know they all involve only static content i.e. not featuring any molecular motions, interactions or any kind of interactivity as our website does, they do not stand web-accessible, most are rather limited in the number of available examples and activities, and a few require ad hoc peripherals.…”
Section: User Adoptionmentioning
confidence: 99%
“…From previous work it is evident that the use of Augmented Reality in education offers many possibilities and advantages to support learning, and this new technology is consistently seen as having enormous potential [3,8,12,13]. Many studies have found an impact on learning gains as well as greater motivation and interest.…”
Section: Introductionmentioning
confidence: 99%
“…AR also enhances collaboration among learners and between learners and instructors. This also enhances critical thinking and problemsolving skills, enhances information processing and communication skills, and improves learning transfer (e.g., [4,6,8,9,[13][14][15]). AR is therefore seen as a sensible tool for learning 21st-century skills and to enable students to explore contexts that are otherwise impossible or too dangerous [1,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Através da bioinformática é possível desenvolver a estruturação de proteínas tridimensionais (3D), o que facilita a procura por sequências de aminoácidos da proteína de interesse que apresentem considerável imunogenicidade referente às suas regiões de estímulo a resposta imune (DAMIÃO, 2019;PETERSON et al, 2020).…”
Section: Introductionunclassified